Czy miłość romantyczna jest emocją? - Dąbrowski, Michał (Kultura i Społeczeństwo, 2020)
The aim of this article is to analyze Raja Halwani’s concept of “romantic love.” Her main thesis is that romantic love is an emotion. The author of the article tries to look at the concept from the perspective of the social sciences, juxtaposing it with selected notions of romantic love from the border of sociology, social philosophy, and theology. He considers that the approach according to which romantic love is presented as an emotional state may be interesting not only for the psychologist but also for the philosopher or sociologist. He points out that love as an emotion is not subject to moral judgments. Finally, he concludes that when considering romantic love from a sociological point of view, its emotional basis should not be overlooked, but closing the phenomenon in the purely emotional sphere seems to be a methodological error.